The Deep Eutectic Solvent in Used Batteries as an Electrolyte Additive for Potential Chitosan Solid Electrolyte Membrane - Kindriari Nurma Wahyusi; Ika Nawang Puspitawati; Abdul Rachman Wirayudha (ASEAN Journal of Chemical Engineering, 2023)
The electrolyte or ion conductor acts as a bridge to transfer the ions the electrodes generate. In general, electrolytes are in the form of liquids. However, liquid electrolytes have drawbacks, including needing to be more practical and leaking quickly. Therefore, people switch to solid matrix electrolytes as battery electrolytes. An ideal solid electrolyte membrane must have chemical stability, thermal stability, high ionic conductivity, high flexibility, low cost, and abundant material availability. Lithium extraction from used batteries using Deep Eutectic Solvent (DES) was found to be an intelligent solvent. Mixing the method with lithium salt on a chitosan membrane can increase conductivity. This study aims to determine the lowest resistance value and highest conductivity of solid polymer electrolytes using Li2CO3 from used batteries. After separating the Lithium-Cobalt component from the used battery, it was extracted with deep DES solvent and precipitated using Na2CO3 to produce the Li2CO3 compound. Polymer electrolyte was synthesized by mixing polyvinyl alcohol and adding 0.2 grams, 0.4 grams, 0.6 grams, 0.8 grams, and 1 gram of chitosan. Li2CO3 variables are 0.2 grams, 0.4 grams, 0.6 grams, 0.8 grams, and 1 gram. The results showed that the higher content of chitosan and Li2CO3 led to an increase in ionic conductivity. These results concluded that the best solid electrolyte membrane was obtained with a variation ratio of 0.2 grams of chitosan with the addition of 1 gram of Li2CO3.